Extrahepatic cholestasis arising from congenital biliary cistern adhesion: a case report - Hariyono, Dedy C.; Ibrohim, Ibnu Sina; Philo, Richard (International Surgery Journal, 2024)
Biliary atresia (BA) is a progressive fibrotic obstructive condition that affects the biliary system, leads bile flow obstruction and the development of newborn jaundice. It is lethal if not treated, with a survival rate of less than 10% by the age of three. Bowel adhesions are anomalous bands of scar tissue that develop between bowel loops. The incidence rate for these bands remains uncertain. This study presents a 2-month-old infant with a progressive yellow discoloration dan diagnosed as BA. Intra operative colangiography was performed and congenital adhesions in the form of bands were discovered.